Causal Factors Affecting Loyalty to Buy Clothes Waterproof Store on Instagram in Thailand - Pornprapai ํYuttapoom; Pankham, Sumaman (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
Instagram is a very popular social media platform and also a quick and convenient online sales channel. Therefore, it is considered an important factor in online shopping. The objectives of this research article were 1) to validate a causal factor affecting loyalty to buying clothes from a waterproof store on Instagram in Thailand and 2) to search the causal factors affecting loyalty to buying clothes from a waterproof store on Instagram in Thailand. This study was quantitative research. The sample was people who bought clothes from waterproof stores on Instagram, a sample of 437 people in Thailand. The tools used in the research were online questionnaires. The statistics used in the data analysis were frequency, percentage, and structural equation model. The results of this research were the development of the causal relationship models, which consisted of 4 components: 1) product quality, 2) price, 3) satisfaction, and 4) loyalty and the model is consistent with the empirical data to a great extent. The statistics show the Chi-square statistics goodness fit test (χ2) = 140.64, degrees of freedom (df) = 115, CMIN/df = 1.22, GFI = 0.97, AGFI = 0.95, SRMR = 0.01, RMSEA = 0.02. The final predictive coefficient is 0.99, which indicates that the variables in the model can explain the variance of the customer loyalty store on Instagram by 99 percent. The causal factor found that product quality, price, and customer satisfaction were found to influence customer loyalty. Use these research results to plan and create strategies that are suitable for customers to build loyalty in the next purchase.